2017
DOI: 10.1002/2016gl072388
|View full text |Cite
|
Sign up to set email alerts
|

Active microwave observations of diurnal and seasonal variations of canopy water content across the humid African tropical forests

Abstract: A higher frequency of severe droughts under warmer temperatures is expected to lead to large impacts on global water and carbon fluxes and on vegetation cover—including possible widespread mortality. Monitoring the hydraulic state of vegetation as represented by the canopy water content will allow rapid assessment of vegetation water stress. Here we show the potential of active microwave backscatter observations at Ku band for monitoring the diurnal and seasonal variations of top‐of‐canopy water content. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 97 publications
3
47
0
Order By: Relevance
“…It is likely that changes in climatic water deficit lead to changes in CWC which ultimately lead to mortality, and future work could explore the temporal and spatial relationship between the three data sets. The use of microwave data to measure CWC could also potentially be used to quantify mortality risk at large spatial scales, particularly in areas prone to heavy cloud cover (Konings et al 2017). Additional overlapping HiFIS and LiDAR data in the future could potentially provide considerable insight into continued drought and/or recovery, as well as the robustness of using CWC changes in a predictive manner.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that changes in climatic water deficit lead to changes in CWC which ultimately lead to mortality, and future work could explore the temporal and spatial relationship between the three data sets. The use of microwave data to measure CWC could also potentially be used to quantify mortality risk at large spatial scales, particularly in areas prone to heavy cloud cover (Konings et al 2017). Additional overlapping HiFIS and LiDAR data in the future could potentially provide considerable insight into continued drought and/or recovery, as well as the robustness of using CWC changes in a predictive manner.…”
Section: Discussionmentioning
confidence: 99%
“…Both active and passive microwave remote sensing data are sensitive to vegetation water status, allowing them to be potentially useful for estimating ecosystem isohydry/anisohydry. Their sensitivities and ability to capture vegetation water status depend on operating frequency, overpass times, and physical properties of the land surface (Jones et al, ; Konings, Yu, et al, ; van Emmerik et al, ). Existing spaceborne records of both active and passive microwave have different characteristics on this front (Paget et al, ; Podest et al, ; Steele‐Dunne et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, Steele-Dunne et al Steele-Dunne et al (2012) modeled L-and C-band backscatter over a forest canopy, and demonstrated that during periods of low soil moisture availability, backscatter is mainly sensitive to changes in vegetation water content. Recent work by Paget et al (2016) and Konings et al (2017) used RapidScat backscatter to confirm that the theorized diurnal cycle over tropical forests definitely exists. In situ data in combination with backscatter is required to test the hypothesis that vegetation water content is the primary driver of water stress related diurnal variation in backscatter.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that radar observations might yield valuable insight into canopy water status. Several studies have identified diurnal variations in backscatter over the Amazon (Birrer et al, 1982;Satake and Hanado, 2004;Frolking et al, 2011;Jaruwatanadilok and Stiles, 2014;Paget et al, 2016) and other vegetated areas (Friesen, 2008;Friesen et al, 2012;Konings et al, 2017). Radar is sensitive to vegetation because of direct backscatter from the canopy, and attenuation of the signal as it travels through the vegetation layer (Ulaby et al, 1982a).…”
Section: Introductionmentioning
confidence: 99%